Statin Safety and Associated Adverse Events: A Scientific Statement From the American Heart Association. Issue 2 (February 2019) - Newman, Connie B.; Preiss, David; Tobert, Jonathan A.; Jacobson, Terry A.; Page, Robert L.; Goldstein, Larry B.; Chin, Clifford; Tannock, Lisa R.; Miller, Michael; Raghuveer, Geetha; Duell, P. Barton; Brinton, Eliot A.; et al.
Abstract : One in 4 Americans >40 years of age takes a statin to reduce the risk of myocardial infarction, ischemic stroke, and other complications of atherosclerotic disease. The most effective statins produce a mean reduction in low-density lipoprotein cholesterol of 55% to 60% at the maximum dosage, and 6 of the 7 marketed statins are available in generic form, which makes them affordable for most patients. Primarily using data from randomized controlled trials, supplemented with observational data where necessary, this scientific statement provides a comprehensive review of statin safety and tolerability. The review covers the general patient population, as well as demographic subgroups, including the elderly, children, pregnant women, East Asians, and patients with specific conditions such as chronic disease of the kidney and liver, human immunodeficiency viral infection, and organ transplants. The risk of statin-induced serious muscle injury, including rhabdomyolysis, is <0.1%, and the risk of serious hepatotoxicity is ≈0.001%. The risk of statin-induced newly diagnosed diabetes mellitus is ≈0.2% per year of treatment, depending on the underlying risk of diabetes mellitus in the population studied. In patients with cerebrovascular disease, statins possibly increase the risk of hemorrhagic stroke; however, they clearly produce a greater reduction in the risk of atherothrombotic stroke and thus total stroke, as well as other cardiovascular events. There is no convincing evidence for a causal relationship between statins and cancer, cataracts, cognitive dysfunction, peripheral neuropathy, erectile dysfunction, or tendonitis. In US clinical practices, roughly 10% of patients stop taking a statin because of subjective complaints, most commonly muscle symptoms without raised creatine kinase. In contrast, in randomized clinical trials, the difference in the incidence of muscle symptoms without significantly raised creatinine kinase in statin-treated compared with placebo-treated participants is <1%, and it is even smaller (0.1%) for patients who discontinued treatment because of such muscle symptoms. This suggests that muscle symptoms are usually not caused by pharmacological effects of the statin. Restarting statin therapy in these patients can be challenging, but it is important, especially in patients at high risk of cardiovascular events, for whom prevention of these events is a priority. Overall, in patients for whom statin treatment is recommended by current guidelines, the benefits greatly outweigh the risks. Abstract : Supplemental Digital Content is available in the text.